The detrimental effect of elemental contaminants when using B additions to improve the creep properties of a Ni-based superalloy. (August 2021) - Detrois, Martin; Pei, Zongrui; Liu, Tao; Poplawsky, Jonathan D.; Gao, Michael C.; Jablonski, Paul D.; Hawk, Jeffrey A.
Abstract: The effect of Si contamination when using B to improve the creep properties of a Ni-based superalloy was investigated using advanced characterization techniques and first-principles simulations on alloys with high and low B levels with varying Si contents. The positive effect of B segregation along grain boundaries on the creep properties was mitigated by the presence of Si which showed a similar segregation preference. Density functional theory calculations were used for validation by calculating grain boundary cleavage energies. Silicon was shown to decrease grain boundary cohesion which offsets the positive effect of B. Graphical abstract: Image, graphical abstract